2008
DOI: 10.1002/bem.20430
|View full text |Cite
|
Sign up to set email alerts
|

Extremely low frequency electromagnetic fields (ELF‐EMFs) induce in vitro angiogenesis process in human endothelial cells

Abstract: Effects of extremely low frequency (ELF) electromagnetic fields (EMFs) on activation of angiogenesis were analysed using cultured umbilical human vein endothelial cells (HUVECs). The cultures were exposed to a sinusoidal EMF to intensity of 1 mT, 50 Hz for up to 12 h. EMFs increased the degree of endothelial cell proliferation and tubule formation, coupled by an acceleration in the process of wound healing. Since this process is physiologically accompanied by a large modification in the structural organization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
43
1
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(53 citation statements)
references
References 34 publications
(43 reference statements)
6
43
1
3
Order By: Relevance
“…However, low-frequency (60 Hz) EF did not affect cell responses, and has actually resulted in decreased phosphorylation levels of ERK. These results are in contrast to previous studies, where profound effects of 50 Hz electromagnetic field on angiogenic processes [60] and MAP kinase activation in HL-60 cells [34] were observed, which may be due to the differences in field orientation used in the present study (field normal to the cell surface) and previous studies (field is parallel to the cell surface), field component (electric in our study and magnetic in Monache et al [60]), or cell type. Previous studies also reported that DC EF of physiological amplitude oriented parallel to the cell plane promoted cell responses such as reorientation, migration, actin assembly and VEGF release in human umbilical cord (HUVEC) and bovine aortic endothelial cells [10,18].…”
Section: Discussioncontrasting
confidence: 99%
“…However, low-frequency (60 Hz) EF did not affect cell responses, and has actually resulted in decreased phosphorylation levels of ERK. These results are in contrast to previous studies, where profound effects of 50 Hz electromagnetic field on angiogenic processes [60] and MAP kinase activation in HL-60 cells [34] were observed, which may be due to the differences in field orientation used in the present study (field normal to the cell surface) and previous studies (field is parallel to the cell surface), field component (electric in our study and magnetic in Monache et al [60]), or cell type. Previous studies also reported that DC EF of physiological amplitude oriented parallel to the cell plane promoted cell responses such as reorientation, migration, actin assembly and VEGF release in human umbilical cord (HUVEC) and bovine aortic endothelial cells [10,18].…”
Section: Discussioncontrasting
confidence: 99%
“…He also shows that 120 mT static magnetic field (SMF) noticeably could reversed the inhibitory effects of TGF-1 on in vitro arteriogenesis, he suggested that SMF could have the potential to modify tubular formation, depending on the origin of the cells and the experimental conditions, including angiogenesis inhibitors or stimulators in the medium used for incubation, field intensity, localization of exposure, exposure duration and heterogeneous or homogeneous magnetic fields [18]. Delle showed some important functions of human micro vascular endothelial cells (in vitro), like proliferation, migration and tube formation are increased under the influence of a sinusoidal electromagnetic field (1 mT, 50 Hz), and the organization of the actin and focal adhesion inside the cell, he shows extremely low frequency sinusoidal electromagnetic fields increased the degree of endothelial cell proliferation and tubule formation and western blot analysis in their research revealed a significant increase in phosphorylation as well as the overall expression of VEGF receptor 2 [19]. Another research done by Chen X and his colleague in 2012, shows inhibitory effects of nanosecond pulsed electric fields on survival of mice with hepato cellular carcinoma with decreases in vascular endothelial growth factor expression and micro-vessel density and apoptosis induction and inhibition of angiogenesis [20].…”
Section: Discussionmentioning
confidence: 98%
“…Pulsed electromagnetic fields were shown to induce vascular endothelial cell growth and angiogenesis through influencing the vascular endothelial growth factor (VEGF)-related pathways. 24,25 In another study, Yuan et al 26 reported induced angiogenesis and the improvement of cardiac function in a surgically-induced infarcted myocardium, after implementing a pulsed magnetic field. In this current study, although in both clinical and histopathologic investigations, there was not a remarkable difference in the rate of stromal neovascularization between the groups; the progression rate of neovascularization over a 2-week period was statistically significant in the magnetic therapy groups and was comparable with the control; such a progression, however, was not observed in the MT group; this was probably due to use of corticosteroids.…”
Section: Discussionmentioning
confidence: 99%